ANALISIS PARAMETER STATISTIK BUTIRAN SEDIMEN DASAR PADA SUNGAI ALAMIAH (STUDI KASUS SUNGAI KRASAK YOGYAKARTA) - Junaidi, Junaidi; wigati, Restu (Wahana Teknik Sipil: Jurnal Pengembangan Teknik Sipil, 2011)
Natural rivers are characterized by a meandering channel with multiple grain-size bed and unsteady flow. Among some of the properties of the sediment grains, the size of the sediment is one of nature's most important and widely used in sedimentation engineering. Grain size greatly affects the easy presence and extent of sediment transported. To study the characteristics of bed material on the sediment transport, various studies have been conducted. This paper examines statistical parameters of grain on the sediment transport from a natural river (River Krasak, Yogyakarta). Variables studied include the classification of grain size, mean (average), standard deviation (sorting), skewness, and kurtosis. Based on the statistical parameters of grain size, the results from three stations showed that bed materials of Krasak 1 are characterized by gravel mode, very poorly sorted, and distributed platikurtic negative skewness. Types of samples are polymodal. Bed materials of Krasak 2 are characterized by the mode of sand, and poorly sorted, and distributed platikurtic very positive skewness. Type of samples are bimodal. While the bed material of Krasak 3 are characterized by sand mode and poorly sorted, and distributed platikurtic very positive skewness. Types of samples are polymodal